Manipulating small water droplets on a photo-switchable mat of fluorinated linear liquid crystal polymers. (June 2020) - Zhang, Xiao; Qin, Lang; Liu, Yuyun; Wei, Jia; Yu, Yanlei
Highlights: The electrospun mat with hierarchical microstructures exhibits fast and reversible superhydrophobic adhesion change. We demonstrate the modulation of 3 μL water droplets on the LLCP mat, which is the smallest volume of water droplets, to our knowledge, that can be controlled by the LCP system. The hierarchical structures remain intact with good fatigue resistance after pinning and removing of the water droplets for several times. Abstract: Manipulating small water droplets on an intelligent surface with tunable superhydrophobic adhesion has attracted considerable interests because of potential applications ranging from no-loss transfer to surface chemistry but remains challenging. Herein, we present a strategy to manipulate the small water droplet on a photo-switchable mat, which is fabricated by a fluorinated linear liquid crystal polymer via electrospinning. The electrospun mat with hierarchical microstructures exhibits fast and reversible superhydrophobic adhesion change, and still remains the superhydrophobicity after pinning and removing of the water droplets for several times. Diverse erasable and rewritable arrays on the vertically placed mat are formed by pinning the small water droplets to any high adhesive position after localized light irradiation. Moreover, after evaporation of the water droplets containing aggregation-induced emission materials, the mat exhibits bright fluorescence upon faint UV irradiation to indicate the trace with the same pattern as the original droplets. Such photo-switchable superhydrophobic mats would provide an open tunable surface for microdroplets manipulation. Graphical abstract: Image, graphical abstract